1993
DOI: 10.2500/105065893781976384
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of the Maxillary Antrum: Anatomic Abnormalities, Diagnostic Difficulties and Surgical Implications

Abstract: ABSTRACfUsing conventional radiography, maxillary sinus hypoplasia (MSH) may be misdiagnosed as chronic infective sinusitis in patients with chronic nasal symptoms. Commonly associated anatomical abnormalities of the lateral nasal wall and orbit may also be missed. Failure to recognize these abnormalities is fraught with hazards should sinus surgery be contemplated on such patients. With the use ofhigh resolution computed tomography scans and rigid nasal endoscopy, MSH and associated subtle anatomic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…This finding should be readily differentiated from those of maxillary hypoplasia with anomalous uncinate formation. 18 Surgical treatment of patients with maxillary sinus atelectasis and enophthalmos is based on two main objectives. The first goal is to obtain adequate clearing of the maxillary sinus and restore a normal drainage pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This finding should be readily differentiated from those of maxillary hypoplasia with anomalous uncinate formation. 18 Surgical treatment of patients with maxillary sinus atelectasis and enophthalmos is based on two main objectives. The first goal is to obtain adequate clearing of the maxillary sinus and restore a normal drainage pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The majority were case reports, with a small number of case series. 7,9,10 In this retrospective study describing a single surgeon's experience, FESS was found to be a safe and effective approach in the management of hypoplastic maxillary sinus related sinusitis.…”
Section: Discussionmentioning
confidence: 96%
“…The reduction in the volume of the maxillary sinus is known as maxillary sinus hypoplasia. Although its origin is unknown, failure of prenatal development has been a major theory; another theory is a poor pneumatization caused by a sinus infection or sinus trauma in childhood 8,9 . This study would provide an excellent opportunity to determine the existence of MSH since prenatal life.…”
Section: Discussionmentioning
confidence: 97%
“…This location is not different from the early reports and corroborates the great relation that both structures maintain during fetal life; in fact, at this stage, the maxillary sinus is an extension of the infundibulum ( Figure 1 ). A poorly developed infundibular passage is associated with MSH, 8,9 evidencing the importance of considering the maxillary sinus and the ethmoid infundibulum as an anatomic and development unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation